Not so Black and White: environmental justice and cumulative impact assessments - Krieg, Eric J.; Faber, Daniel R. (Environmental impact assessment review, 2004)
A growing number of scientific studies in recent years have investigated disparate exposure to ecological hazards in American society. Working from an environmental justice perspective, this body of research consistently reveals that poor communities of color are most likely to bear a disproportionate burden of negative externalities. These studies utilize a wide range of research methodologies, including various indicators of ecological hazards (e.g., proximity to waste sites, industrial emissions, ambient air quality), but few, if any, utilize composite measures to approximate cumulative environmental impact. Consequently, the environmental justice (EJ) literature is characterized by a failure to effectively measure overall impact from an extensive range of ecological hazards. Limitations on available data make this a serious problem for present and future studies. We argue that cumulative measures of environmental impact can play an important role in furthering our understanding of environmental injustices in the United States. In this study of Massachusetts, we develop and implement such a cumulative measure of negative environmental impacts. By controlling for the density and severity of ecological hazardous sites and facilities within every community in the state, we demonstrate that exposure patterns take a generally linear distribution when analyzed by race and class. So, while our results reaffirm previous findings that low-income communities and communities of color bear significantly greater ecological burdens than predominantly White and more affluent communities, our findings also suggest that environmental injustices exist on a remarkably consistent continuum for nearly all communities. In other words, as the minority population and lower-income composition of a community increases, correspondingly, so does cumulative exposure to environmental hazards. In this respect, communities which are more racially mixed and of moderate income status that are not typically identified as meeting EJ criteria (in demographic terms) also face more significant ecological hazards. Thus, the strict bifurcation of communities into categories of Environmental Justice and Non-Environmental Justice is problematic, and poses a serious dilemma for policy makers, public health officials, and community activists. To overcome this challenge requires the adoption of a cumulative environmental justice impact assessment (CEJIA), which in addition to the demographic characteristics of a community, also takes into account the total environmental burden and related health impacts upon residents. Furthermore, through the adoption of the precautionary principle, source reduction, and alternative forms of “cleaner” production, environmental justice advocates must work for policies which reduce the environmental threat for the full range of communities, as well as their own.